Osmotically dehydrated microwave-vacuum drying of strawberries - V. Changrue (2018)
Strawberries were osmotically dehydrated prior to microwave-vacuum drying. Drying kinetics were presented in terms of the temperature of the product during drying, drying curve and drying time. Thin-layer models of Lewis, Henderson and Pabis, and Page were fitted with the observed data. The root mean square error and the coefficient of determination (r2) were used to evaluate the fit of the models. The effects on quality of dried strawberries were evaluated for various drying parameters such as: with or without osmotic treatment, input power levels (1 W/g and 1.5 W/g) and power modes (continuous, 45 s on/15 s off, 30 s on/30 s off). The effects were evaluated by a standard factorial (2 × 2 × 3) analysis in triplicate. The quality aspects were studied in terms of water activity, shrinkage, rehydration capacity, texture, color and sensory evaluation. The results showed that the osmotic pretreatment did not help in terms of drying time and energy saving but provided a better quality of dried product. Page's model presented the best fit for the observed data. © 2008 Wiley Periodicals, Inc.